Synthesis and characterisation of nano alumina dental filler. (2nd February 2009) - Al-Haik, Marwan; Hanson, Caleb; Luhrs, Claudia; Tehrani, Mehran; Phillips, Jonathan; Miltenberger, Scott
The production of alumina nanoparticles using a low power plasma torch and creating a nanocomposite for use in dental applications were investigated. Upon fabricating the nanocomposite based on alumina nanoparticles, the mechanical properties were studied using instrumented nanoindentation and compared to three standard dental fillers. Several nanocharacterisation techniques were employed in the current study for these dental fillers and for natural dental materials; enamel and dentine. The mechanical tests carried out in this investigation include nanoindentation and nanoscratch. The newly developed nanocomposite outperformed the commercial nanocomposite in hardness and elasticity. However, the results of the mechanical tests suggest that the silver amalgam had the best mechanical properties among the four dental fillers investigated.